SAK ETAP and Village-Owned Enterprises (BUMDes) in Java: A Systematic Literature Review - Widiyati, Dian; Sinaga, Yoshe Lawrin (Kompartemen : Jurnal Ilmiah Akuntansi, 2025)
This study examines the implementation of SAK ETAP in preparing financial reports for Village-Owned Enterprises (BUMDes) in Java Island and identifies challenges in compliance. SAK ETAP is a streamlined accounting standard designed to guarantee accountability and transparency in financial reporting for organisations that are not subject to public scrutiny, such as Village-Owned Enterprises (BUMDes). This research applies a qualitative approach through a Systematic Literature Review using the PRISMA method. A total of 14 relevant studies published between 2020 and 2024 were analyzed. The findings show that most Village-Owned Enterprises (BUMDes) have not fully adopted SAK ETAP, primarily due to limited accounting knowledge, lack of competent human resources, and insufficient government support. Some Village-Owned Enterprises (BUMDes) only prepare cash-based records or partial financial statements, leading to low comparability and reliability. The study emphasizes the importance of training, technical guidance, and standardized reporting systems to improve compliance. The results contribute by providing insights for policymakers, regulators, and stakeholders to strengthen governance and accountability in Village-Owned Enterprises (BUMDes) financial management.